From Coherence in Theory to Coherence in Practice - Hammerness, Karen (Teachers College Record, 2006)
Historically, one of the central concerns that has plagued the field of teacher education is the observation that fragmentation characterizes the experience of learning to teach. Too often, university-based teacher education programs consist of a set of disconnected individual courses; separate clinical work from coursework; and lack a vision of teaching and learning. Therefore, some teacher educators have argued that creating structurally and conceptually coherent programs will result in more powerful learning for prospective teachers. Yet, although empirical work on such programs is growing, there is little research on the nature of coherence and on how it might develop. To that end, this article documents one teacher education program’s efforts to become more coherent, focusing on the ways in which the program tries to become more coherent and on the challenges of coherence. The article concludes with implications for teacher education program design and evaluation, with a focus on the power, complexity, and problems of coherence.